2017
DOI: 10.1097/htr.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise for Adolescents With Prolonged Symptoms After Mild Traumatic Brain Injury: An Exploratory Randomized Clinical Trial

Abstract: Objective To describe the methodology and report primary outcomes of an exploratory randomized clinical trial (RCT) of aerobic training for management of prolonged symptoms after mild traumatic brain injury (mTBI) in adolescents. Setting Outpatient research setting Participants Thirty adolescents between the ages of 12 and 17 years who sustained a mTBI and had between four and 16 weeks of persistent symptoms. Design Partially blinded, pilot RCT of sub-symptom exacerbation aerobic training compared to a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
2
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(177 citation statements)
references
References 78 publications
5
156
2
14
Order By: Relevance
“…Common methodological limitations included lack of a control group, lack of randomisation and lack of control for confounders. One RCT demonstrated positive effects with multimodal physiotherapy21 and two RCTs evaluated the effects of subsymptom threshold aerobic exercise training—one identifying a positive effect22 and the other found no difference with training 23. The other RCT evaluated collaborative care, including advocacy and coordination with schools regarding accommodations and motivational interviewing, cognitive–behavioural therapy (CBT) and psychopharmacological consultation 24.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common methodological limitations included lack of a control group, lack of randomisation and lack of control for confounders. One RCT demonstrated positive effects with multimodal physiotherapy21 and two RCTs evaluated the effects of subsymptom threshold aerobic exercise training—one identifying a positive effect22 and the other found no difference with training 23. The other RCT evaluated collaborative care, including advocacy and coordination with schools regarding accommodations and motivational interviewing, cognitive–behavioural therapy (CBT) and psychopharmacological consultation 24.…”
Section: Resultsmentioning
confidence: 99%
“…Athletes in the submaximal exercise groups typically reported fewer symptoms, recovered to baseline on cognitive and balance scores faster, and in one study34 demonstrated more efficient activation patterns on functional Magnetic Resonance Imaging (fMRI) relative to matched controls. One RCT in adolescents demonstrated a positive treatment effect with subsymptom exacerbation aerobic training on symptom ratings; however, poorer adherence to exercise was reported in the aerobic training group compared with the stretching group 79. The other RCT demonstrated no difference between groups in time to recovery 80…”
Section: Discussionmentioning
confidence: 99%
“…One RCT,21 one quasi-experimental study,24 and three small case series16 17 23 demonstrated a reduction in symptoms, improvement in exercise tolerance and return to normal lifestyle and sport participation in patients treated with an individualised subsymptom threshold aerobic exercise programme.…”
Section: Resultsmentioning
confidence: 99%
“…5 Structural connectivity analysis has emerged in recent years as a novel approach that quantifies brain connectivity based on the topological characteristics of the entire network. 6 With this approach, the brain network is modelled as a system comprised of functionally associated but spatially segregated grey matter regions integrated by white matter tracts that transfer information critical for the normal functioning of the network.…”
Section: Introductionmentioning
confidence: 99%